2016
DOI: 10.1007/s12663-016-0904-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Evaluating the Risk of Thromboembolic Events During Dental Extractions

Abstract: Dental extractions can be safely carried out in patients on anti-platelet therapy without the risk of significant post-extraction bleeding thus averting the risk of thromboembolic events that might take place on temporary discontinuation of antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…Although it is known that the dual use of these agents significantly decreases the risk of thromboembolism, it has also been stated that patients receiving dual therapy have a significant risk of hemorrhage during dental surgical procedures. 7 In this present study, hemorrhage rate was similar among the subgroups as one patient on acetylsalicylic acid subgroup, one patient on clopidogrel subgroup, and two patients on dual therapy subgroup. Extraction sockets were packed with gelatin sponges after granulation tissue was curetted following the dental extractions, and a dry gauze compress was applied for 10 minutes in this study as a standard protocol described in literature.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Although it is known that the dual use of these agents significantly decreases the risk of thromboembolism, it has also been stated that patients receiving dual therapy have a significant risk of hemorrhage during dental surgical procedures. 7 In this present study, hemorrhage rate was similar among the subgroups as one patient on acetylsalicylic acid subgroup, one patient on clopidogrel subgroup, and two patients on dual therapy subgroup. Extraction sockets were packed with gelatin sponges after granulation tissue was curetted following the dental extractions, and a dry gauze compress was applied for 10 minutes in this study as a standard protocol described in literature.…”
Section: Discussionsupporting
confidence: 65%
“…14 A previous literature review showed that there is a very limited number of studies evaluating the hemorrhage risk at the same times as major or minor operations take place, even if it's a simple dental extraction. 7,[15][16][17] Eighty-two patients who underwent a single or multiple dental extraction operations were evaluated by Krishan et al 17 researchers reported that they did not encounter any prolonged hemorrhage, and they concluded that it is unnecessary to interrupt antiplatelet therapy before simple dental extractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 articles were deemed potentially relevant. Once the full text was analyzed, a total of 5 articles were included in this review: Gaspar, 1999 (17); Ardekian, 2000 (18); Medeiros, 2011 (19); Varghese 2015 (20) and Sadhasivam 2016 (21) ( Table 2, Table 2 continue: Characteristics of included studies). Of the 20 articles in which its full text was reviewed, 15 were excluded from this review as they didn´t meet the inclusion criteria ( Table 3, Table 3 continue).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 articles in which its full text was reviewed, 15 were excluded from this review as they didn´t meet the inclusion criteria ( Table 3, Table 3 continue). From the included studies, 2 were conducted in Israel (17,18), 1 in Brazil (19), 2 in India (20,21). Only one specifies in which setting it was conducted, being that, a medical center (18).…”
Section: Resultsmentioning
confidence: 99%